Promoting walking and cycling new perspectives on sustainable travel - Pooley, Colin 1950-; Jones, Tim 1972- (Policy Press, 2013)
This book uses innovative research methods to examine why so many people fail to travel in ways that are deemed by most to be desirable - on foot or by bike. It proposes evidence-based policy solutions that could increase levels of walking and cycling substantially